Design Actions for Shifting Conditions - Berlingieri, Fabrizia; Cavallo, Roberto; Corradi, Emilia; de Boer, Hans (TU Delft Open, 2022)
A spatial lens on Climate Change dynamics in urban transitions considering the growing importance that the urban environments assume within contemporary territorial transformations yet little room is offered within market-driven societies to critically reflect the spatial impact that cities face vis-à-vis the urgencies for environmental rebalancing. It embraces a wide range of phenomena we all live and experience nowadays, not only incidentally but more in a structural way, forcing us to rethink our present state and explore futures. Transitions embody the fluctuating form of late capitalism with its raisings and disruptions. Regarding the environmental conditions, they are affecting the world regions' habitability, the phenomenon of progressive urbanization versus agricultural land abandonment (UN 2018). With these premises, transitions seem to be a proper reference for an interdisciplinary and conceptual frame addressing the transformation of urban and metropolitan contexts, which will be the leading players for the coming decades.